Electrical and thermal properties of bisphenol A propoxylate diglycidyl ether-piperazine copolymer/functionalized MWCNT composites - Yilmaz, Serpil; Pekdemir, Mustafa Ersin; Coskun, Mehmet (Serbian Chemical Soc, 2018)
In this work, bisphenol A propoxylate diglycidyl ether-piperazine copolymer functionalized MWCNTs (oxidized MWCNT + aminated MWCNT) composites were prepared and structurally characterized using FTIR and NMR spectroscopy. The composites were investigated in terms of their electrical and thermal properties. The surface morphology of the composites was examined by SEM. It was observed that thermal stability decreased while the ac conductivity and dielectric constant (relative permittivity) increased with increasing functionalized MWCNT content (2, 5, 10 and 15 mass %) of the composites. The electrical conductivity increased with increasing temperature and the activation energy of ac conductivity was determined and discussed.
Keywords: bisphenol A; piperazine; MWCNT; composite; copolymer